Arboreal Tropical Forest Vertebrates: Current Knowledge and Research Trends - R. W. Kays; Allison, A. (Tropical Forest Canopies: Ecology and Management, 2001)
We review the ecology and specialized methods required for studying arboreal mammals, birds, reptiles and amphibians, and use faunal checklists from 12 tropical wet forest sites and an analysis of all articles published during the past ten years in 14 major journals to assess current knowledge and general research trends for these groups. The percentage of arboreal vertebrates was remarkably similar at the different sites (76.2 ± 3.9%). Birds were the most arboreal group and amphibians and reptiles the least. The review of journals showed that primates were overwhelmingly the most studied group (336 papers), followed by bats (105), passeriform birds (73) and rodents (55). Judging by their portion of the arboreal vertebrate community and the number of papers surveyed, birds and amphibians and reptiles are vastly understudied compared to mammals, but this is largely due to the great number of primate studies. The number of publications on arboreal vertebrates has remained relatively stable over the last 10 years for all taxa except primates, which have seen a growth in publications. Canopy vertebrates from Brazil had by far the most publications (120), followed by Madagascar (61), Costa Rica (55) and Indonesia (42). We conclude by highlighting the priorities we see for future studies on tropical canopy vertebrates.
Keywords: Amphibians; Birds; Canopy Mammals; Primates; Reptiles